Analysis of the Influence of Product Quality, Price Perception, and Packaging on Purchasing Decisions and Their Impact on Consumer Satisfaction of Bluder Bread Products - Untari, Dewi; Safirin, Mochamad Tutuk; Tirkaamiana, Dean; Lantara, Dirgahayu (Journal La Sociale, 2023)
CV. XYZ is a food-related company that uses a make-to-order production system and sells bread as its primary product. CV. XYZ encounters issues with the low degree of customer satisfaction with Bluder Bread’s product quality, cost, and packaging as well as the drop-in number of purchases made by customers. This study aims to ascertain how purchase decision are influenced by product quality, perceived pricing, and packaging, as well as how these factors affect customer happiness. Partial Least Square (PLS) based Structural Equation Modeling (SEM) analysis is used in the investigation. The research conclusions demonstrated that, although packaging did not significantly influence decisions to buy, percepstions of product quality and pricing had a major impact. However, customer satisfaction with bread was not significantly impacted by product quality, perceptions of pricing, or packaging. Purchase decisions can serve as a mediator and have a big impact on customer happiness.